Sub-acute and acute toxicity of Ferula asafoetida and Silybum marianum formulation and effect of the formulation on delaying gastric emptying - Ramanaiah Illuri; Sudeep Heggar Venkataramana; David Daguet; Shyamprasad Kodimule (BMC, 2019)
Abstract Background Delayed gastric emptying play an important role in the pathology of functional dyspepsia. Owing to their functional attributes in alleviating the gastrointestinal disorders, single or polyherbal formulations have gained attention to treat the symptoms of functional dyspepsia. We have investigated the safety and efficacy of a novel formulation of Ferula asafoetida oleo resin and standardized Silybum marianum extract (Asdamarin). Methods The effect of asdamarin on delayed gastric emptying was investigated in Sprague Dawley rats using phenol red method. The acute and sub-acute oral toxicity was evaluated in wistar rats following OECD guidelines 425 and 407 respectively. The data were analyzed by one-way ANOVA using GraphPad Prism 5.0 software. Results Oral administration of Asdamarin dose-dependently improved the delay in gastric emptying as evident from the significant increase in the gastrointestinal transit time (p < 0.001). The LD50 of asdamarin was estimated to be more than 2000 mg/kg. Further, in the 28-day sub-acute toxicity study, the administration of 250, 500 and 1000 mg/kg of Asdamarin did not significantly altered the feed and water consuption, body weight change, biochemical and haematological parameters compared to control animals. Macroscopic and histopathological examination of vital organs revealed no toxic signs. Conclusion The preliminary data from the present study provides the first evidence on the possible effectiveness of novel formulation of F. Asafoatida and S. marianum extracts in alleviating the associated symptoms of functional dyspepsia. The toxicity data indicated that Asdamarin can be considered safe up to 1000 mg/kg dose.